A Comment on "College Enrollment and Mandatory FAFSA Applications: Evidence from Louisiana" - Guillaume Morlet; Thi Kim Dung Dang; Mirinda Anderson (Institute for Replication (I4R), 2025)
Christa Denault (2023) examines the effect of a policy implemented in Louisiana that mandates that high school students are required to complete the FAFSA as part of the requirements to graduate high school. In her preferred specification (equation (1)), she used a two-way fixed effects estimation strategy, with a continuous treatment dose to find that the mandate increased FAFSA completion rates by 19 percent and implied an increase in college enrollment of 1 to 2 percentage points. She complements this result with an event study to test for parallel trends, and finally an instrumental variable estimation. First, we find that the paper is computationally reproducible. We focused on the reproduction of Tables 2 and 3 and Figure 2. Second, we document that the author's results are largely robust. The author's treatment variable is the FAFSA completion rate. When we substitute this by the FAFSA submission rate, the author's results remain qualitatively identical. We also find that the IV results are robust to many alternative specifications. Furthermore, the parallel trends assumption, and no treatment assumption made by the author for the specification in equation (1) (inherent to difference-in-difference estimation) seems robust.
Keywords: 330